Pacing and team strategy in relay events in swimming - McGibbon, K.; Pyne, D.; Shephard, M.; Osborne, M.; Thompson, K. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Interest in medal winning opportunities in swimming relays has grown with the addition of mixed events at the FINAWorld Championships and the 2020 Olympics. Although pacing is considered crucial for success in individual events, there is a lack of research examining pacing in relays. Performance in relays may be affected by the order swimmers are placed within a team. The purpose of this study was to compare pacing strategies in relay events with corresponding individual events, and examine the relationship between team selections and performance. Race data from FINAWorld Championships between 2011-2017 including 50-m splits and overall race time were analysed retrospectively. A total of 256 (128 male, 128 female) 4 x-200-m freestyle relay final swims involving 192 swimmers were analysed. Individual 200-m freestyle season`s best time for the same year was located using FINA world rankings. There was no substantial impact of pacing strategy on 200-m freestyle performance, except positive pacing led to slower times in individual events for females. Relay swimmers are typically faster in the first half of their 200-m leg, but slower in the second half, when compared with their individual events. Approximately half of the swimmers changed pacing strategy when competing in relay events. The majority of relay teams placed their first or second ranked swimmer on the lead-off leg, and their third or fourth ranked swimmer on the third leg. Successful team strategies were different for males and females, although the quality of the swimmers in a team also plays a role.